2012
DOI: 10.5923/j.ajgis.20120101.01
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing and Geographic Information Techniques: Veritable Tools for Land Degradation Assessment

Abstract: Land degradation can be defined as land which due to natural processes or human activity is no longer able to sustain properly its economic function and/or its original natural ecological function. The implications of the land use-land cover change often lead to land degradation. This study used Landsat TM image of 1986 and Nigeriasat-1 image of 2008 to assess the degraded lands for the respective years in a section of Niger Delta, Nigeria. The data sets were analysed using Arcview software in the Geographic I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Other studies suggest that degradation of the Niger Delta mangroves has occurred since at least the 1980's. Abbas and Fasona [76] and Abbas [49] found a roughly three-fold increase (10.6% to 32.2%) in mangroves and marshland classed as degraded between 1986 and 2008. Omo-Irabor et al [33] found a decrease of 15% in mangrove population between 1987 and 2002 by comparing Landsat imagery between those two years.…”
Section: Niger Delta Nigeriamentioning
confidence: 98%
“…Other studies suggest that degradation of the Niger Delta mangroves has occurred since at least the 1980's. Abbas and Fasona [76] and Abbas [49] found a roughly three-fold increase (10.6% to 32.2%) in mangroves and marshland classed as degraded between 1986 and 2008. Omo-Irabor et al [33] found a decrease of 15% in mangrove population between 1987 and 2002 by comparing Landsat imagery between those two years.…”
Section: Niger Delta Nigeriamentioning
confidence: 98%
“…Land use-land cover change analysis enable planners and policy makers to have adequate knowledge on what should be done to have equitable development that will be sustainable and eco-friendly [1]. Land wh ich is the ult imate resource of the biosphere refers to a specific area of the earth surface with physical entity encompassing its topography and spatial nature [2].…”
Section: Introductionmentioning
confidence: 99%